2016
DOI: 10.1016/s2213-8587(16)00053-x
|View full text |Cite
|
Sign up to set email alerts
|

Active commuting and obesity in mid-life: cross-sectional, observational evidence from UK Biobank

Abstract: Background: This study examines the relationship between active commuting (AC) and obesity in mid-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
94
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 18 publications
10
94
1
6
Order By: Relevance
“…These errors greatly affect the quality of the samples (1)(2)(3)(4). Currently, substantial efforts are being undertaken worldwide to set up high-quality standardized biobanks that will store billions of sample aliquots, including those from national cohort studies (5)(6)(7)(8)(9)(10)(11). An important goal of these national cohorts is to draw precedent-setting conclusions for use by national healthcare systems (12,13 ).…”
mentioning
confidence: 99%
“…These errors greatly affect the quality of the samples (1)(2)(3)(4). Currently, substantial efforts are being undertaken worldwide to set up high-quality standardized biobanks that will store billions of sample aliquots, including those from national cohort studies (5)(6)(7)(8)(9)(10)(11). An important goal of these national cohorts is to draw precedent-setting conclusions for use by national healthcare systems (12,13 ).…”
mentioning
confidence: 99%
“…Recientemente, Cummins y cols., en un estudio que incluyó 156.000 participantes del UK Biobank en el Reino Unido, reportaron que personas que realizan transporte activo, en comparación a los que se transportan en vehículos, presentan menores niveles de IMC (-1,71 y -1,65 kg/m -2 en hombres y mujeres, respectivamente.) 5 . La magnitud de la asociación reportada es mayor que la encontrada en nuestro estudio, no obstante, ambos muestran una tendencia y dirección similar en sus resultados.…”
Section: Comparación Con Estudios Previosunclassified
“…Una de las limitantes mencionadas por la revisión fue la heterogeneidad existente entre estudios, destacando que la mayor parte de la evidencia proviene de estudios escandinavos, quienes por cultura han practicado transporte activo por mucho más tiempo que otros países. Los autores destacan de manera especial la carencia de evidencia en países no desarrollados, ya que, la realidad sociocultural de estos países podría presentar resultados completamente diferentes a aquellos reportados en países desarrollados 5,[14][15][16][17][18][19] . Si bien la evidencia en relación a los beneficios del transporte activo en la reducción de la adiposidad es conflictiva, hay sólo un estudio que muestra que cambiar el modo de transporte de activo (caminar o andar en bicicleta) a inactivo (automóvil) incrementa los niveles de adiposidad .…”
Section: Comparación Con Estudios Previosunclassified
See 1 more Smart Citation
“…However, there seems to be a dose-response relationship between physical activity and health benefits in healthy subjects, increasing the health benefits with increased activity levels [14]. A recently published cross-sectional study showed that walking or riding a bike to work reduced total body fat compared to driving, even though the intensity of the activity was low [15]. In another study it was shown that reducing the amount of walking from 6000 to 1500 steps daily negatively affected insulin sensitivity, reduced lean mass and increased fat mas in both young and older subjects [16,17].…”
Section: Recommended Levels Of Physical Activitymentioning
confidence: 99%